The Role of the Sabhara Patrol Unit in Preventing the Circulation of Alcohol in the Jurisdiction of the Tasikmalaya City Police - Holmes Juan Daniel Batubara (Advances in Police Science Research Journal, 2021)
The existence of alcohol in Indonesia is limited by government regulations, including in the City of Tasikmalaya. The local government issued the City of Tasikmalaya Regional Regulation Number 7 of 2015 concerning Control and Supervision of Alcoholic Beverages in the City of Tasikmalaya which states that the people of Tasikmalaya City are prohibited from distributing and consuming alcoholic beverages. Based on the initial observations the authors found that the circulation of alcohol in the City of Tasikmalaya is still very high. In overcoming the problem of liquor circulation, it is necessary to take decisive steps and actions from law enforcement, one of which is the police. This research is a research with a qualitative approach. The data sources for this research are primary data sources and secondary data sources. Then, the data collection techniques used in writing this thesis are observation, interviews, and document studies. Furthermore, to test the accuracy and validity of the data in this study, the triangulation technique was used. Data analysis techniques in qualitative research are data reduction, data presentation, and conclusion drawing. This study also uses Role Theory, Crime Prevention Theory, Management Theory, Patrol Concepts and Liquor Concepts. The results of the study show that the circulation of liquor in the jurisdiction of the Tasikmalaya City Police is still rampant and very difficult to eradicate. The role of the Sabhara Unit in preventing the circulation of liquor in the jurisdiction of the Tasikmalaya City Police is to carry out patrols and handle tipiring. The factors that influence the Patrol Role of the Sabhara Unit in preventing the circulation of liquor in the jurisdiction of the Tasikmalaya City Police are supporting factors, namely facilities and infrastructure factors, support from other functions, Tasikmalaya City Regional Regulation Number 7 of 2015, as well as public attention and support as well as the inhibiting factors, namely the number of police personnel at the Tasikmalaya City Police, the amount of DIPA budget that is getting here is decreasing, the patrol strategy is permanent, and the participation of the community.